If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(3s + 6) = 315 Reorder the terms: 7(6 + 3s) = 315 (6 * 7 + 3s * 7) = 315 (42 + 21s) = 315 Solving 42 + 21s = 315 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-42' to each side of the equation. 42 + -42 + 21s = 315 + -42 Combine like terms: 42 + -42 = 0 0 + 21s = 315 + -42 21s = 315 + -42 Combine like terms: 315 + -42 = 273 21s = 273 Divide each side by '21'. s = 13 Simplifying s = 13
| 12y+60x=120 | | 3(2i+10)=78 | | r^4+2r^3+r^2= | | 5x+8=-41-2x | | 7t-2t-5t=9+13 | | 5(a-7)=50 | | 4x/15=6/5 | | 13*4-8=x | | 2+11x=-58+x | | (e+1)*4=20 | | 15700+26883-3579= | | 2r^2-2r-1= | | 7-6+15x+9x=49 | | n^2-22+120=0 | | -2s+3=-5s+24 | | 3+x-5=4+2(x-1) | | 6x+14+9=41 | | 4*cos*2*x=1 | | (-5x)(-6y)(2z)= | | x=2700+.1x | | 5+x=2x-(-3) | | 7+30x=20x+13 | | 2x-16x^(-1/2)=0 | | 2x-16x^-1/2=0 | | 30-5x=12-7x | | (x+1)(2x^2-9x-4)=0 | | 4x+7=-17-2x | | y=2x-3x+2y+14 | | [5y+(5x+4)][5y-(5x+4)]=0 | | 70x+10-54x-6=45x+45 | | 5(2x+1)=x+30 | | 48+9x=-3 |